Improving delivery performance in seller, carrier and customer triad : Outbound transport perspective - Jylhä, Miio (fi=Turun yliopisto|en=University of Turku|, 2018)
Outbound transportation process is a part of order-to-delivery process and it sustains the flow of finished goods from manufacturing plant, through the distribution network until delivery reaches retailer or end customer. Managing this process plays a crucial role in meeting customer’s expectations and maintaining manufacturing company’s competitiveness. This thesis aims to recognize challenges in case company’s outbound transportation process, its practices and relations embedded that may impair delivery performance from customer point of view. The case company is a large technology company and the assignment was conducted as a case study. The data about case company’s outbound transportation process was gathered through multiple interviews, process walks and analysis of reports with primary attention on challenges potentially burdening delivery performance. The outbound transportation process is affected by the case company, carriers and customers, thus it is inspected through triadic perspective in order to assess the causation of one entity’s actions on others and the whole. The theoretical framework through which the process is investigated was put together with the triad model as the frame, which then was complemented with customer expectations, inefficiencies ingrained in the process in addition to uncertainties caused by parties, exogenous factors, sub processes and communication. Uncertainty and inefficiencies derived from one entity cause disruptions for other parties and the whole chain hindering the process’s ability to perform punctually and efficiently. Challenges was recognized in all parts of the chain. From interface of production and forwarding, transport time variability and issues in reporting to communication in triad. In case company sub optimizing parts of the process without consideration of whole stood out as performance disrupting challenge. In addition to challenges related to meeting the customer expectations the thesis unfolds procedures decreasing cost performance from case company’s point of view.